2007
DOI: 10.1155/2007/90169
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Angiosarcoma Presenting as an Acute Intraabdominal Hemorrhage Treated with Transarterial Chemoembolization

Abstract: Primary malignant neoplasms of the liver are some of the most uncommon malignancies in many parts of the world. They include hepatocellular carcinoma and stromal tumors such as hepatic angiosarcoma. It is a lethal tumor with life expectancy of less than six months. Once discovered, it is often too late for surgical intervention. Like other vascular tumors of the liver and spleen, intraperitoneal hemorrhage is a well-documented finding of angiosarcoma which can be lethal if not diagnosed and treated immediately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…reported a PHA patient who underwent right lobe transjugular liver biopsy (three separate biopsies) and only showed nonbridging portal fibrosis, extensive sinusoidal fibrosis, and panlobular in some areas, and at last the patient was diagnosed after liver transplant . Failure or mistake of diagnosis by CT or ultrasound‐guided fine‐needle aspiration biopsy has also been reported by different institutions . What is more, Egea et al .…”
Section: Imaging and Pathological Diagnosismentioning
confidence: 98%
See 1 more Smart Citation
“…reported a PHA patient who underwent right lobe transjugular liver biopsy (three separate biopsies) and only showed nonbridging portal fibrosis, extensive sinusoidal fibrosis, and panlobular in some areas, and at last the patient was diagnosed after liver transplant . Failure or mistake of diagnosis by CT or ultrasound‐guided fine‐needle aspiration biopsy has also been reported by different institutions . What is more, Egea et al .…”
Section: Imaging and Pathological Diagnosismentioning
confidence: 98%
“…31 Failure or mistake of diagnosis by CT or ultrasound-guided fine-needle aspiration biopsy has also been reported by different institutions. [32][33][34][35][36] What is more, Egea et al 35 reported a PHA patient who had peritoneal bleeding 48 h after fine-needle biopsy, and Rademaker et al 21 reported a patient who developed a huge subcapsular hematoma after biopsy. Therefore, nonsurgical biopsy is generally avoided, and open liver biopsies or laparoscopy will be more accurate and safe.…”
Section: Imaging and Pathological Diagnosismentioning
confidence: 99%
“…There have also been reports of arterial chemoembolisation in localized osteosarcoma 14 and hepatic angiosarcoma. 15,16 Percutaneous ethanol injection involves introducing single or multiple fine needles into the metastatic lesion and injecting ethanol (90-100%), thus causing cell death mainly by M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 13 dehydration. 17 A randomized trial of 232 patients with small hepatocellular carcinomas demonstrated those treated with radiofrequency ablation to have significantly longer survival compared to those treated with percutaneous ethanol injection.…”
Section: Accepted Manuscript 12mentioning
confidence: 99%
“…[ [4][5][6][7][8] TACE has shown improved patient survival rates compared to conservative treatment for various types of malignant liver tumors.…”
Section: [1-3]mentioning
confidence: 99%
“…[5][6][7][8] This combination produces elevated local chemotherapeutic drug levels along with vascular occlusion of the feeding vessels killing the tumor resulting in reduced systemic toxicity without causing collateral damage to the surrounding liver parenchyma.…”
Section: [1-3]mentioning
confidence: 99%